2018
DOI: 10.1016/j.seizure.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of recurrent afebrile seizures in children with benign convulsions associated with mild gastroenteritis

Abstract: All the recurrent afebrile seizures initially diagnosed as CwG, irrespective of the kinds and frequency of relapses, showed favorable prognoses. CwG maybe falls within the category of situation-related seizures, rather than epilepsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 33 publications
6
32
0
Order By: Relevance
“…Previous studies have shown a favorable prognosis for BCWG [ 7 , 10 ]. The recurrence rate of BCWG has been reported to range from 7.7–16.8% in earlier studies [ 7 , 11 ]. Here, we report similar favorable long-term outcomes: two out of 44 children who completed long-term follow-ups had recurrent seizures that did not develop into epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown a favorable prognosis for BCWG [ 7 , 10 ]. The recurrence rate of BCWG has been reported to range from 7.7–16.8% in earlier studies [ 7 , 11 ]. Here, we report similar favorable long-term outcomes: two out of 44 children who completed long-term follow-ups had recurrent seizures that did not develop into epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…BCWG seizures are often clustered, with generalized tonic-clonic seizures forming the most common type of seizure cluster, although focal or secondary generalized seizures are also observed [ 7 , 12 , 15 ]. Consistent with previous reports, we found that tonic or generalized tonic-clonic seizures were the most common types of seizures associated with BCWG; however, it is very likely that BCWG originated as a focal event as spikes were observed in the EEG tests that were localized to various regions of the cortex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognosis of CwG is good, with the affected children developing normally before and after seizures and having no disability even when experiencing clustered seizures during the acute stage [2,7,30,31]. Progression to epilepsy from CwG has been rarely reported [7,8,22,24].…”
Section: Clinical Characteristicsmentioning
confidence: 99%
“…CwG are benign convulsions that occur between the ages of 6 months and 3 years, with this age range first defined by Komori et al [3] in 1995. However, the age range of patients with CwG has been estimated in the literature as being as broad as from 1 month to 6 years [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][22][23][24][25][26]30,31]. Hypoglycemia, an electrolyte imbal-ance such as hyponatremia or hypocalcemia, and central nervous system infection that can trigger seizures have to be excluded in this definition .…”
Section: Introductionmentioning
confidence: 99%